Effects of Muscle Thickness of Masseter and Sternocleidomastoid, Forward Head Posture and Breathing in Subjects With and Without Dentures - Se-Yeon Kim; Ki-Song Kim; Young-In Hwang (Korean Research Society of Physical Therapy, 2022)
Background: For the elderly, masticatory function is one of the most important oral func-tions and the masticatory ability is related to the wearing of dentures. Many older people wear dentures for their masticatory function, but a significant number of older people who use dentures have found that they feel uncomfortable when performing their daily activities, such as performing masticating functions or talking.Objects: The purpose of this study is to investigate how the forward head posture (FHP), respiratory function and thickness of masseter (MS), and sternocleidomastoid (SCM) are af-fected by the presence or absence of dentures in the elderly, and what kind of correlation there is between these variables.Methods: The study was conducted on 11 patients in the normal group and 13 in the denture group. The participant's cognitive ability was evaluated using Mini-Mental State Ex-amination Korean (MMSE-K), and the FHP was evaluated by measuring the craniovertebral angle (CVA). The thickness of the MS and SCM muscles were measured using ultrasound, and respiration was measured with a spirometry. As for the statistical method, the correlation of each variable was investigated using Spearman's correlation coefficient.Results: In the normal group, there was a significant correlation between forced vital capac-ity (FVC) and forced expiratory volume in 1 second (FEV1) (p < 0.001), and in the denture group, FVC and FEV1 (p < 0.001), maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP) (p < 0.001), CVA and Lt. MS (p = 0.012).Conclusion: CVA and Lt. MS of the denture group have a high negative correlation, it is related that the thickness of MS may be thick when the elderly wearing dentures are FHP.